1982
DOI: 10.1136/thx.37.9.676
|View full text |Cite
|
Sign up to set email alerts
|

Lung tissue volume estimated by simultaneous radiographic and helium dilution methods.

Abstract: The pulmonary total tissue volume (blood, extravascular water, and dry tissue volume) was measured by finding the difference between the radiographic displacement volume of the thorax (RDVT) and the lung gas volume. Simultaneous determinations of RDVT and gas volume were made in 10 healthy subjects sitting upright. RDVT was determined from posteroanterior and lateral chest radiographs, a computerised modification of the Barnhard method being used; and gas volume was measured by helium dilution with each radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Armstrong et al report that at FRC tissue accounts for 19% of total lung volume (2). For each subject, 1 liter was subtracted from the measured lung volume at FRC ϩ 1, and 19% of this value was taken as the lung tissue volume for that subject.…”
Section: Methodsmentioning
confidence: 99%
“…Armstrong et al report that at FRC tissue accounts for 19% of total lung volume (2). For each subject, 1 liter was subtracted from the measured lung volume at FRC ϩ 1, and 19% of this value was taken as the lung tissue volume for that subject.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was done on euthanized pigs; hence, ϕ was constant. Previous studies [42, 58] suggest that the lung air volume fraction ϕ = 75 % [1], the lung tissue density ρ p = 1000 kg/m 3 , and the air density in the lung ρ g = 1.21 kg/m 3 . Hence, the composite lung parenchymal density would be given by: ρ=ϕρp+false(1-ϕfalse)ρt…”
Section: Methodsmentioning
confidence: 99%
“…Direct measurements volume was derived from tissue weight, on the of the diameters of included and excluded vessels, assumption that air free lung tissue has a specific made with a pair of screen cursors, showed that the gravity of 1 -04. The reproducibility of this technique boundary excludes any blood vessels with diameters was checked by applying it on 10 occasions to one 12 subjects withfibrosing alveolitis (squares) and in 12 with chronic airflow limitation (triangles). SLC predicted represents 47-5% ofthe plethysmographic measure oftotal lung capacity apportioned to the left lung and the remainder to the right lung.8 The mean (SD) error in SLCct was 370 (381) ml.…”
mentioning
confidence: 99%
“…Fig5 A comparison ofactual and interpolated estimates of the area ofcomputed tomography slices ofsingle lungs in (left handpanel) 12 subjects withfibrosing alveolitis (squares) and in (right handpanel)12 subjects with chronic airflow limitation (triangles). In practice, departuresfrom the line ofidentity will on average befour times less than those shown here.…”
mentioning
confidence: 99%